Light Emitting Diodes in the Experimental Practice for the Characterization of Novel Photovoltaics. Issue 1771 (2015) - Pravettoni, Mauro; Manni, Loris; Dittmann, Sebastian
ABSTRACT: Light Emitting Diodes (LEDs) have recently gained importance in the experimental practice of photovoltaic (PV) devices. LEDs have already been proposed as the alternative to conventional xenon or halogen based solar simulators. Multi-junction PV devices use coloured LEDs in experimental tools as well: LEDs can transform a conventional solar simulator in a spectrally adjustable simulator for spectral characterization of multi-junction modules. Other useful applications include evaluating the dependence of the electrical parameters on the average photon energy and spectral responsivity measurements of multi-junction PV devices.